Effect of hydrogen cyanamide (HC) on release of floral bud dormancy, endogenous hormone and carbohydrate in Pyrus pyrifolia cv. Cuiguan - LIU Dongfeng; CHEN Lulu; LI Guopeng; WANG Tao; TENG Yuanwen (浙江大学学报. 农业与生命科学版)
Bud dormancy is an adaptive developmental process for perennial deciduous fruit trees to survive under the adverse environmental conditions, which is released when both the chilling requirement and growth temperature are achieved. Prolonged dormancy is considered to be the major obstacle to economic production of temperate fruits in warm winter regions. In Southern China, due to warm winter temperature, dormancy release becomes a major factor for production of Pyrus pyrifolia cv. Cuiguan. The irregular blossoming and delayed flowering behavior present in this crop may cause negative influence on pear industry of this region. In view of limiting factor in particular regions, the need for artificial means to compensate for lack of natural chilling for maintaining economic production of pear crop. Chemicals likewise hydrogen cyanamide (HC) and thiourea is widely used to overcome the bud release problem of insufficient chilling for deciduous fruits. P. pyrifolia is a good early maturing cultivar and commercially grown in the region of Southern China. Now, Hydrogen cyanamide (HC) was used as a dormancy breaking agent for P. pyrifolia. Different concentration of hydrogen cyanamide (HC) was used to release floral buds from dormancy and duration of dormancy releasing periods of buds, to analyze the variation in endogenous hormones and carbohydrates.Survey was made during the phenological periods including floral bud breaking, flowering and fruit maturing and investigation were made by enzyme-linked immunosorbent assay (ELISA) for the occurrence of changes in endogenous hormone contents including gibberellin (GA3), abscisic acid (ABA) and zeatin riboside (ZR) and the data was recorded for carbohydrate conversion between starch and soluble sugar in floral bud.Data regarding phenological phase were analysed statistically. Results presented indicated that higher concentration of hydrogen cyanamide treatment (2%) was significantly proved better for early bud break and also in florescence period (both the initial flower stage and full-blossom stage). However, all the level of HC treatment did not affect significantly on frutescence period, the fruit firmness and total soluble solid content. As far as endogenous hormone content changed in floral bud after hydrogen cyanamide treatment, gibberellins contents showed the tendency like ‘ascent-decent-ascent’, in early days of application, while after twenty days, at 2% concentration, HC caused a significant increase in endogenous GA3, those were higher level as compared to non treated sample (control). Obtained results further depicted that the maximum contents of abscisic acid (ABA) was yielded as a result of hydrogen cyanamide treatment as compared to other endogenous hormones. The rise in endogenous hormones (ABA and GA3) as a result of the higher HC dose may be due to direct stimulation of ABA and GA3 synthesis by HC.Keeping the presented results in view, it might be presumed that abscisic acid would play an important role in dormancy release after hydrogen cyanamide treatment. Moreover the conversion from starch to soluble sugar in floral bud indicates that the activity of meristem is increased with the dormancy release.Therefore, on the basis of obtained results it is concluded that hydrogen cyanamide treatment could overcome the problem of prolonged dormancy and shorten the bud dormancy release period without affecting the fruit quality i.e. firmness, sugar content and total soluble solid.